A Preliminary Laboratory Study of Initial Copper Release from Dredge Residuals. Issue 2 (March 2014) - Karim, M. A.; Bunch, Barry W.; Schroeder, Paul R.
<x xml:space="preserve">Abstract</x> A preliminary laboratory study was conducted to investigate the impact of different residual types and sediment surface roughness on copper contaminant fluxes to the water column. Sediments from Torch Lake, Michigan served as the test samples. These sediments are mining by‐products with elevated Cu levels. Six experiments were run during which the sediments were conditioned to simulate different forms of residuals. During these experiments, the water column above the sediments was circulated via peristaltic pumping or orbital shaking and the total and dissolved Cu levels were monitored periodically for 15 days. Dissolved Cu levels indicated that during the first 48 hr the water column concentrations approached equilibrium for all six cases. Total Cu levels increased with time and did reach equilibrium but were more susceptible to fluctuations in water column suspended solids levels. Analysis of the resulting dissolved Cu data indicated that the resulting water column Cu concentrations differed with sediment surface and residual type. The highest dissolved Cu water column concentrations were observed for a roughened surface with a larger surface area. The lowest water column dissolved Cu levels were observed for the case with sediment slurry placed over clean sand. The dissolved Cu levels in the water column for all six simulated conditions were several orders higher than the USEPA ambient water quality criteria for protection of aquatic life. © 2014 Wiley Periodicals, Inc.*